Study on the Effects of Feeding and Starvation on the External Morphology and Gonadal Development of Artificially Matured American Eel - Lan Wang; Jialun Liu; Zhongmei Yang; Tongxi Ai; Feng Zhao; Keji Jiang; Lei Gao; Mingfei Li; Ye Ding; Na Zhao; Wei Jiang; Xinhui Wei; et al. (Fishes, 2026)
The aim of this study is to investigate how external nutrient supply affects the allocation of reproductive energy during artificial ripening of American eels (Anguilla rostrata), as well as the physiological regulatory mechanisms involved in their bodies. Healthy female American eels were selected for the experiment and randomly divided into two groups: feeding group and starvation group (simulating the natural migration of American eels without eating). The initial weight of the feeding group was (308.43 ± 36.99 g), and the initial weight of the starvation group was (291.67 ± 63.31 g). The entire experiment was divided into two stages: the first stage was a 6-month nutritional reinforcement period, during which the feeding group was regularly fed with Vannamei shrimp, while the starvation group was not fed throughout the entire process. The second stage was a 3-month artificial ripening stage, during which both groups of eels stopped feeding. Inject 1 mL of mixed hormone (containing 6.5 mg of carp pituitary extract CPE+200 IU human chorionic gonadotropin HCG per mL per week) into each eel for a total of 12 injections to induce gonadal maturation. Both groups of eels did not die during the experiment, with a survival rate of 100%. As the gonads continue to develop and mature, the growth and development advantages of the feeding group of eels are very obvious: body weight, chest circumference, and gonadal index are significantly higher than those of the starvation group. After completing 12 hormone injections, the gonadal index of the feeding group reached (32.72 ± 7.01%), while that of the starvation group was only (4.35 ± 2.48%). Under artificial ripening conditions, the egg diameter of the feeding-eel group increased rapidly in the later stage of the experiment. The growth rate of eggs in the starvation group was slow, and the final egg diameter was significantly smaller. The diameters of the nuclei of both groups of oocytes increased synchronously with the progress of the experiment; the number of nucleoli in the feeding group first increased and then decreased, while the number of nucleoli in the starvation group continued to increase. The oil droplets inside both sets of eggs gradually increased in size, and the oil droplets fed to the eggs in the middle and late stages of maturation had a larger volume. Hormone test results showed that the testosterone (T) level in the eel fed group increased significantly in the later stage of the experiment. This indicates that adequate nutrition can alleviate the inhibition of the reproductive endocrine axis through positive feedback regulation of the pituitary gonad (BPG) axis. Nutritional reinforcement before ripening can promote gonadal development and enhance reproductive capacity by regulating the distribution of nutrients between muscles and gonads. The results of this study provide a solid theoretical basis for improving the nutritional management plan for parent fish in the fully artificial breeding process of American eels.